Application of RC flexural theorems for member design under elevated temperature. (15th December 2019) - Yuan, Fang; Wu, Yu-Fei
Highlights: The new flexural theorems are applied for derivation of flexural design equations. RC flexural design under elevated temperature is simplified using stress block method. The method applies when nearly uniform temperature field forms in RC plastic hinge zone. Results from the simple calculations are consistent with fire test results. Abstract: Equivalent rectangular stress block is widely used for flexural design of reinforced concrete (RC) members. Conventionally, stress block parameters are obtained from extensive flexural tests of RC beams and columns. Parameters of the stress block are closely related to properties of concrete. Therefore, new stress block parameters are required when new materials, such as high-performance concrete, are used in construction, or materials face unusual scenarios such as higher temperature. Structural testing under elevated temperature is difficult and expensive, and hence, insufficient tests have been undertaken so far to derive the stress block parameters. This work produces stress block parameters for RC members under elevated temperature without doing experimental tests. By applying the newly developed RC flexural theorems, which were mathematically derived and applicable to general RC members, the relevant stress block parameters are obtained. This facilitates the flexural design of RC members under elevated temperature by engineers using the conventional stress block approach. The flexural behavior of RC members under elevated temperature is further studied, through parametric studies.